Chelation-assisted formation of multi-yolk–shell Co4N@carbon nanoboxes for self-discharge-suppressed high-performance Li–SeS2 batteries. Issue 35 (22nd August 2019) - Chen, Tao; Kong, Weihua; Fan, Mengting; Zhang, Zewen; Wang, Lei; Chen, Renpeng; Hu, Yi; Ma, Jing; Jin, Zhong
Abstract : A chelation competition induced polymerization strategy was exploited to prepare multi-yolk–shell Co4 N@carbon nanoboxes, greatly enhancing the overall performance of Li–SeS2 batteries. Abstract : Selenium sulfides are considered attractive cathode materials for lithium storage due to their higher specific capacities than elemental selenium and better electrical conductivity than sulfur. However, due to the dissolution of intermediate polyselenides and polysulfides, selenium sulfides suffer from fast capacity degradation and low coulombic efficiency. Herein, we report a chelation competition induced polymerization (CCIP) strategy for the synthesis of multi-yolk–shell Co4 N@carbon (MYS-Co4 N@C) nanoboxes as an advanced SeS2 host material, which can simultaneously achieve good rate capability and cycling stability. Due to both physical confinement by carbon shells and strong chemical affinity of polar Co4 N yolks, the MYS-Co4 N@C nanoboxes can restrict the outward diffusion of S x 2− and Se x 2− intermediates to suppress self-discharge and boost cycling stability. Benefitting from the high metallic conductivity and catalytic activity of Co4 N, the SeS2 -filled MYS-Co4 N@C composite cathode also shows good electron/ion transport properties, and thus the redox kinetics and utilization ratio of the SeS2 active material can be improved. As a result, a high specific capacity retention and a superior rate capability can be achieved at a high SeS2 loading content of 70 wt%. When the mass loading of SeS2 is increased to 4.5 mg cm −2, the composite cathode still exhibits high reversible capacity and stable cycle performance.